Outlook on Finnish cargo owners’ scope 3 emission reductions - Ertiö, Titiana; Saurama, Antti (Finland, 2026)
Managing scope 3 emissions from transportation is challenging since transport chains are often complex, global, multimodal, and involve numerous stakeholders. The role of transport within total scope 3 emissions can differ widely depending on the value chain and transport chain characteristics of a focal company. Scope 3 emission reductions make emission approaches less straightforward than controlling a company’s own emissions.